Justice, Diversity, and Dialogue: Rawlsian Multiculturalism - Peetush, Ashwani Kumar (2014)
In this chapter, I argue that John Rawls’ later work presents one of the most fruitful liberal frameworks from which to approach global cultural diversity. In his Law of Peoples (1999), the normative architecture Rawls provides is much more open to an intercultural/religious dialogue with various non-Western communities, such as the First Nations, than are other liberal approaches. Surprisingly, this has gone unnoticed in the literature on multiculturalism. At the same time, Rawls’ framework is not problem free. Here, I am concerned with Rawls’ conception of overlapping consensus as political, rather than comprehensive; or the idea that dialogue and discussion concerning issues of justice must necessarily, as a matter of principle, exclude philosophical or religious reasons. I argue that this constraint will only add to the unfair exclusion of legitimate concerns. I demonstrate this in Rawls' discussion of so-called non-public spiritual perspectives of land, non-human animals, and the environment – views strikingly similar to those held by many Indigenous and Native Americans. Rawls’ framework unjustifiably and unjustly excludes such views from participation in the public and political realm. In the context of a globally diverse world, and in light of a history of Western colonialism, oppression, and domination of Indigenous peoples, I would argue that justice and fairness require that such others at least be able to articulate their concerns in the public and political domain, according to their own self-understandings and as they see fit, even if we do not agree with these. I argue that Rawls’ proviso is insufficient as a response.